Influence of Biopolymer Synthesized from Tamarind Seed Polysaccharide (TSP) on Seed Quality Parameters of Maize Hybrid COH(M) 8 - Sivasakthi, S.; Renganayaki, P. R.; Sundareswaran, S. (Research Highlights in Agricultural Sciences Vol. 7, 2023)
The current study looks at the effect of a biopolymer synthesized from Tamarind Seed Polysaccharide (TSP) on the seed quality of a maize hybrid. The experiment was carried out in Department of Seed Science and Technology, Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu during 2021. Biopolymer was synthesized from Tamarind Seed Polysaccharide (TSP) and added with different additives and coated on maize seeds. The polymer coated seeds were evaluated for its physiological and biochemical parameters. The seeds were given with four treatments viz.,T0- control (untreated seed), T1- biopolymer (B.P) - 10g kg-1, T2- B.P (10g) + Humic acid (0.3g) + Zimmu (Allium cepa × Allium sativum) leaf extract (0.5 ml) and T3- T2+ Ascorbic acid (0.2 g) and evaluated for seed quality parameters. The findings of the current investigation showed that T3 was significantly superior viz., greater percentage of germination (95%), rate of germination (31.64), seed metabolic efficiency (2.78), seedling root length (25.92 cm), seedling shoot length (15.57 cm), total biomass production (9.41 g), vigour index I (3942), vigour Index-II (94.15). This treatment also recorded greatest value of biochemical parameters such as \(α\)-amylase (2.23), dehydrogenase (1.87 OD value), catalase (29.94) and peroxidase (7.00) activities. It decreased the percentage of abnormal seedlings (2%), dead seeds (3%), days to 50% germination (2.54), mean emergence time (3.02) and pathogen infection (0.25%). We concluded that T3-coated maize seeds had improved seedling establishment and are recommended as a pre-sowing seed treatment in organic agriculture.